2021
DOI: 10.1057/s41599-021-00823-9
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 and the academy: opinions and experiences of university-based scientists in the U.S.

Abstract: Much of the available evidence regarding COVID-19 effects on the scientific community in the U.S. is anecdotal and non-representative. We report findings from a based survey of university-based biologists, biochemists, and civil and environmental engineers regarding negative and positive COVID-19 impacts, respondent contributions to addressing the pandemic, and their opinions regarding COVID-19 research policies. The most common negative impact was university closures, cited by 93% of all scientists. Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
3
20
0
Order By: Relevance
“…A few recent studies have found that some challenges due to the COVID-19 pandemic largely relate to a poor work environment, limited access to resources, new allocation of workloads, and lack of informal contact with colleagues for doctoral students and other researchers [49,50]. A survey study conducted in March 2020 targeting university-based biochemists, biologists, and civil engineers found that university closure and disruption of lab work emerged as the most negative COVID-19 impacts for the majority of participants (88-93%) [23]. Similarly, we found that a large group of our survey participants in STEMM fields experienced emerging challenges for their academic labors due to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A few recent studies have found that some challenges due to the COVID-19 pandemic largely relate to a poor work environment, limited access to resources, new allocation of workloads, and lack of informal contact with colleagues for doctoral students and other researchers [49,50]. A survey study conducted in March 2020 targeting university-based biochemists, biologists, and civil engineers found that university closure and disruption of lab work emerged as the most negative COVID-19 impacts for the majority of participants (88-93%) [23]. Similarly, we found that a large group of our survey participants in STEMM fields experienced emerging challenges for their academic labors due to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Scores for each scale were calculated by summing the scores for the relevant subscales. The severity of depression was divided into normal (score 0-9), mild (10)(11)(12)(13), moderate (14-20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (�28). The total anxiety score was divided into normal (0-6), mild (7)(8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe (�20).…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…The outbreak of Covid-19 has brought in many challenges globally that has put a cold grips on almost all sectors of the global economy [17] and disrupted the business world [18]. Covid-19 pandemic has brought in unprecedented implications in informal entrepreneurial activities around the globe [19]. The informal workers and enterprises are the most affected by the Covid-19 pandemic in Africa through lockdown, social distancing and travel bans, [20].…”
Section: Introductionmentioning
confidence: 99%